Guided Peer Review to Improve Students’ Essay Writing Competence: A Classroom Action Research - Imas Wahyu Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2020)
Feedback in oral as well as written form from both teachers and peers is commonly practiced in language learning at all levels. However, there are a limited number of researches referring to the effect of peer feedback on essay writing competence. Peer feedback can promote independent learning, yet, it may raise questions on its reliability. This study tries to reveal whether guided peer review gives any significant improvement on young adults' essay writing performance on their achievement test. Eight students of the One Year English Program at LIA Pramuka were involved in several sessions of essay writing activities, followed by peer correcting sessions guided by peer review checklist, and revising sessions. Pre-test and post-test were used to determine the improvement on such aspects of essay writing as organization, content, grammar, and vocabulary. It was found that most participants became more aware of how to write a well-organized and comprehensive essay although few still cannot perform well at the post-test. In contrast, this study revealed that peer checking cannot significantly help the students write well-structured sentences and choose appropriate diction. Since this study involves a small number of students, further research engaging more students and in more varied levels are encouraged.